Determining appropriate set volume for resistance exercise - Krieger, J. (Strength and Conditioning Journal, 2010)
Determining the appropriate number of sets per exercise is an important part of designing a resistance training program. Evidence from a recently published meta-analysis indicates that 2-3 sets per exercise produce 46% greater strength gains than a single set. Little benefit is observed for more than 3 sets. For clients interested in general fitness or who lack time, a single set is appropriate. Three sets per exercise is an appropriate starting point for clients looking for maximal strength gains. Adjustments can be made from these starting points based on client response.